Mapping ground deformation in the northern Yangtze River estuary using improved MT-InSAR based on ICA and non-stationary analysis - Zhijie Zhang; Songbo Wu; Guoqiang Shi; Xiaoli Ding; Chaoying Zhao; Bochen Zhang; Liang Chen; Zhong Lu (Geo-spatial Information Science)
Coastal regions are increasingly vulnerable to ground deformation hazards, which can cause structural damage and amplify flood risks. Accurately monitoring the evolution of such deformation is crucial for hazard assessment. However, the precision of multi-temporal interferometric synthetic aperture radar (MT-InSAR), a powerful geodetic technique for mapping ground deformation, is often compromised by the atmospheric phase screen (APS) effect. This is more serious in coastal zones, where it can bias the detection of deformation turning points and mislead the interpretation. In this paper, we introduce a novel approach that designs a non-stationarity test for independent component analysis (ICA) to effectively separate the APS and deformation phase components in MT-InSAR applications. Through simulated experiments, the proposed method demonstrated a 50% improvement in deformation accuracy and can effectively track deformation progression. We validated the new method with a case study in Nantong, a coastal region along the northern Yangtze River estuary in China, using Sentinel-1 data from 2015 to 2023. The proposed method retrieved the ground deformation over Nantong with a root-mean-square-error (RMSE) of less than 5.6 mm when compared to ground leveling measurements, which surpasses the traditional MT-InSAR methods. The study results identified diverse ground deformation patterns in Nantong, with deformation rates ranging from −56.3 to 45.9 mm/year, attributed to groundwater extraction, urbanization activities, and land reclamation efforts. The study also highlights the significant coastal accretion and land reclamation processes in the study area, demonstrating the potential capability of the MT-InSAR technique in detecting coastal erosion detection and informing land reservation.